Evaluation of Policies to Accelerate the Elimination of Extreme Poverty in Lebak Regency, Banten Province - Rahayu, Sierfi; Rizkiyani, Tiwi (Future Science, 2025)
Extreme poverty is an issue that is a global, national and even local focus. Unlike ordinary poverty, extreme poverty is not only a condition of inability to meet basic needs but is seen from accessibility to social service places and even from the expenditure side, where extreme poverty is IDR 10,739 per day and only IDR 322,170 per month. The purpose of this study is to determine how to evaluate accelerating the eradication of extreme poverty in Lebak Regency. The theory used is from Stufflebeam (2003) with four aspects of evaluation: context evaluation, input evaluation, process evaluation, and product evaluation. The research method used is descriptive qualitative. The results of this study indicate that the policy objective of accelerating the elimination of extreme poverty in Lebak Regency has been achieved, where there was a decrease in extreme poverty from 1.67% to 0.82% in 2024. The policy of accelerating the eradication of extreme poverty in Lebak Regency needs to be carried out sustainably by increasing periodic monitoring and evaluation, as well as developing innovations in the Gebyar KLASIK program